Oral health-related knowledge, practice and their associated factors among mothers in a rural municipality of Eastern Nepal - Gautam, Ujwal; Shrestha, Ashish; Bhagat, Tarakant; Agrawal, Santosh Kumari; Sah, Ram Bilakshan (Journal of Nepalese Association of Pediatric Dentistry, 2022)
Introduction: Oral Health status in children has been shown to be related with oral health patterns learned through the childhood. The children acquire health behaviors from their mothers.Objective: This study aims to assess the oral health related knowledge and practice among mothers in a rural municipality of Eastern Nepal and explore the factors associated with these outcomes.Methods: A randomly selected 268 women either pregnant or having children of less than 6 years of age were interviewed in April- June, 2019 to assess their knowledge and practice regarding oral health. Data was entered using Epidata 3.1. Response on knowledge and practice were presented as frequency and proportion and compared with different maternal variables using inferential statistics.Results: Mean age of the participating women was 25.9 years (SD 5.3). Three participants were pregnant (primigravida). Majority (96.7%) of respondents reported brushing their teeth at least once a day. Only 9.3% reported using fluoridated toothpaste for their children. Similarly, majority (69.4%) of participants had knowledge about wiping baby’s gums after breastfeeding or after letting child bottle feed. Literacy was found to significantly influence the participants’ brushing frequency, brushing technique, practice of brushing or wiping their child’s teeth and gums.Conclusions: Oral health related knowledge among mothers and their practice were found to be unsatisfactory across several domains. Further, these outcomes were found to be influenced by several maternal characteristics. Assessing knowledge-practice gap on oral health resulting from maternal characteristics can provide a basis for providing training to women on necessary parenting skills.